Examining The Linkage Between Work-Life Balance and Psychological Well-Being Among Employees - Sri Hartini; Adeline Videlia Kosasih; Verincia Ghoward; Audrey Elysia Cong; Winida Marpaung (IJIP : Indonesian Journal of Islamic Psychology, 2025)
The main focus of this study is to delve into the connection between psychological well-being and work-life balance among employees at PT. Asia Paramita Indah Medan. A purposive sampling technique was used to select 95 employees aged 20-60 years as participants. Data was collected using a psychological well-being scale consisting of 48 items and a work-life balance scale with 40 items. Data analysis was performed using SPSS 23. Normality and linearity tests were run to ensure the validity of the results. In order to examine the relationship between psychological well-being and work-life balance, the data collected was analyzed with Pearson Correlation. Results showed a negative correlation with value -0.446, indicating an inverse connection between psychological well-being and work-life balance among employees. The effective contribution was 19.9%, suggesting that additional variables not considered in this study may impact the remaining percentage, which provides a perspective for further studies.